MECHANISM OF HUOXUE HUAYU DECOCTION PROMOTING TIBIAL FRACTURE HEALING IN RATS VIA NOTCH1/PPARG/CD36 SIGNALING PATHWAY - Fei Zhao; Mian Wang (Journal of Animal and Plant Sciences, 2025)
Objective: Tibial fractures are a common type of traumatic injury, typically treated through surgical reduction and fixation; however, the healing outcomes are often suboptimal. The aim of this work was to investigate the mechanism by which Huoxue Huayu Decoction influences tibial fracture healing in rats via Notch1/PPARγ/CD36 pathway. Materials and methods: A total of 48 male Sprague-Dawley rats of clean grade were randomly rolled into control group (sham surgery, 10 mL/kg/d saline gavage, n=12), model group (fracture model, 10 mL/kg/d saline gavage, n=12), positive group (fracture model, 0.27 g/kg/d Xianling Gubao capsule gavage, n=12) and HXHYT group (fracture model, 13.45 mL/kg/d Huoxue Huayu Decoction gavage, n=12). Rats in each group were administered gavage once daily for 28 consecutive days. X-ray imaging and the Lane-Sandhu score were employed to assess tibial fracture healing. Enzyme-linked immunosorbent assay (ELISA) detected serum levels of inflammatory cytokines and bone formation markers. Tibial tissue from the rats was collected to measure biomechanical parameters. Western blot analysis detected the expression of bone-regulatory factors. Results: Relative to control group, model group showed a reduced Lane-Sandhu score, elevated serum levels of inflammatory cytokines TNF-α, IL-1β, IL-6, and bone formation markers alkaline phosphatase (ALP), bone gla protein (BGP), and insulin-like growth factor-1 (IGF-1), as well as a decrease in tibial maximum load, elastic load, and maximum deflection. Additionally, tibial BMP-2, RUNX2, VEGF, Notch1, and CD36 protein levels were increased, while tibial PPARγ protein expression was decreased (P<0.05). In comparison to model group, positive group and HXHYT group exhibited an increased Lane-Sandhu score, decreased serum levels of TNF-α, IL-1β, and IL-6, elevated serum levels of ALP, BGP, and IGF-1, and increased tibial maximum load, elastic load, and maximum deflection. Tibial BMP-2, RUNX2, VEGF, Notch1, and CD36 protein levels were increased, while tibial PPARγ protein expression was decreased (P<0.05). Relative to positive group, HXHYT group showed more pronounced improvements in all indicators (P<0.05). Conclusion: Huoxue Huayu Decoction can modulate the Notch1/PPARγ/CD36 pathway to alleviate inflammation in tibial fracture rats, improve the biomechanical function at the fracture site, and effectively promote fracture healing.
Keywords: tibial fracture; Huoxue Huayu Decoction; inflammation; biomechanics; Notch1/PPAR?/CD36 pathway